Bangladesh’s story of change in nutrition: Strong improvements in basic and underlying determinants with an unfinished agenda for direct community level support - Nisbett, Nicholas; Davis, Peter; Yosef, Sivan; Akhtar, Nazneen (Elsevier, 2017)
Bangladesh has made considerable progress in reducing child stunting and is lauded as a success story in global nutrition fora. This mixed-methods study considers available statistical and qualitative evidence to help reveal the critical factors behind Bangladesh's ‘story of change’ in nutrition. Much of the improvement in nutrition in Bangladesh in recent years is explained by what can be seen as nutrition-sensitive drivers within a wider enabling environment of pro-poor economic growth. Key amongst these factors have been improving incomes; smaller family sizes and greater gaps between births; parental - and particularly women's - education and wider health access. Research and interviews with key stakeholders and work at a community level has helped shed light on the policy and programmatic choices which lie behind these wider determinants. Community based nutrition programmes have not yet been operating at scale as in other countries and the current governance arrangements for nutrition delivery are weak. But as Bangladesh faces growing new nutritional problems and still suffers from a relatively high burden of child stunting, such ‘nutrition-specific’ programmes will have to play a greater role than in the past, as the further gains from some of these wider drivers may be limited and are likely to have plateaued.